2004
DOI: 10.1037/0002-9432.74.3.272
|View full text |Cite
|
Sign up to set email alerts
|

The Extension of School-Based Inter- and Intraracial Children's Friendships: Influences on Psychosocial Well-Being.

Abstract: Children's (N=142) school friendships with same versus different race peers were coded for prevalence and the extent to which parents maintained social relationships with these friends (a proxy for extension of friendships beyond the school context). Membership in integrated versus nonintegrated social networks at school was unassociated with psychosocial well-being. Out-of-school extension of interracial friendships was linked with greater social competence among Black children. Black children whose friendshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…European American and African American children who heard explicit information about racism expressed greater valuing of racial fairness than their peers who did not receive explicit lessons about racism. Racial fairness valuing may lead children to form interracial friendships, which have been linked to higher levels of social competence and self‐esteem among elementary‐school‐aged children (Fletcher, Rollins, & Nickerson, 2004), and to lower levels of racial prejudice among middle school children (Damico, Bell‐Nathaniel, & Green, 1981). Additionally, learning about racism was associated with greater lesson satisfaction among African American children and with greater endorsement of counterstereotypic information among older European American children.…”
Section: Discussionmentioning
confidence: 99%
“…European American and African American children who heard explicit information about racism expressed greater valuing of racial fairness than their peers who did not receive explicit lessons about racism. Racial fairness valuing may lead children to form interracial friendships, which have been linked to higher levels of social competence and self‐esteem among elementary‐school‐aged children (Fletcher, Rollins, & Nickerson, 2004), and to lower levels of racial prejudice among middle school children (Damico, Bell‐Nathaniel, & Green, 1981). Additionally, learning about racism was associated with greater lesson satisfaction among African American children and with greater endorsement of counterstereotypic information among older European American children.…”
Section: Discussionmentioning
confidence: 99%
“…More research is needed on processes that may facilitate youths’ ability to interact with diverse peers in positive and effectual ways. The ability to engage effectively across ethnic/racial groups has implications for other important social and developmental outcomes (e.g., Bagci, Rutland, Kumashiro, Smith, & Blumberg, ; Fletcher, Rollins, & Nickerson, ; Lease & Blake, ) as well as later educational experiences (e.g., college), the workforce, and positive intergroup relations in broader society (e.g., Gieling, Thijs, & Verkuyten, ; Gurin, Dey, Hurtado, & Gurin, ; Jayakumar, ; Kawabata & Crick, , , ; Pettigrew & Tropp, ; Reimer et al., ; Saleem, Yang, & Ramasubramanian, ). Indeed, this capacity is part and parcel of youths’ social awareness and relationship skills , which are two of the five core social‐emotional competencies promoted by the Collaborative for Academic, Social, and Emotional Learning (i.e., CASEL 5; Weissberg, Durlak, Domitrovich, & Gullotta, ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Studies comparing same‐ and cross‐ethnic friendships have consistently found a preference for same‐ over cross‐ethnic friendships among children as young as 3 years (Aboud et al., 2003; Boulton & Smith, 1996; Fishbein & Imai, 1993; Graham & Cohen, 1997; Hamm, Brown, & Heck, 2005; Kao & Joyner, 2004). Apart from being more seldom than same‐ethnic friendships, cross‐ethnic friendships seem to be primarily school based and rarely extend beyond the school context (Aboud & Amato, 2001; Fletcher, Rollins, & Nickerson, 2004).…”
Section: Longitudinal Trajectory Of Cross‐ethnic Friendships In Childmentioning
confidence: 99%